Influência da adição de rejeitos cerâmicos nas propriedades de cerâmica vermelha da região do Recôncavo Baiano - Santos, Osvaldo Cruz (2007)
The study of the physical and mechanic properties is an analysis of unquestioned importance on the production of the ceramic materials. In the region of the Recôncavo Baiano, there are ceramic and small brick factories, that still use rudimentary techniques, where the necessity of characterization of raw materials is denounced by the quality of the final product. The present work has for objective to study the behavior of the clay proceeding from the region of the Recôncavo, between the cities of Candeias and Camaçari/Ba, with addition of 5, 10 and 15% by weight of brick scraps, trying to optimize the physic and mechanical properties of the final product, aiming a better possibility of being manufactured, mechanic resistance, low linear retraction and water absorption. The brick scraps and the clay were characterized by FRX, DRX, TG, ATD and the granulometric analysis. Samples for testing where prepared by uniaxial pressing at 25Mpa, in 60x20x5mm size. The evaluated technological properties were: linear retraction, water absorption, apparent porosity and flexural strength. The samples were burned in electric oven in the temperatures of 850º, 950º and 1050ºC and compared its mechanical properties and the gresification. With addition of 15% by weight of brick scraps and burning at 900º-1000ºC the samples showed properties superior to that clay